Pengaruh CR, DAR dan NPM Terhadap EPS Pada PT Unilever Indonesia Tbk Periode 2018-2022 - Fitri, Anisa; Rakhmanita, Ani (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2023)
The research background is the evaluation of company performance in estimating the profit per share that will be obtained by investors when investing which is seen in the value of earnings per share. The amount of earnings per share is obtained by comparing the net profit after tax with the number of shares in the financial statements. This study aims to determine the simultaneous and partial effect of the current ratio, debt to asset ratio and net profit margin on earnings per share. The type of research being carried out is research using statistical quantitative methods, data analysis methods using multiple linear analysis, classic assumption tests and hypothesis testing using IBM SPSS statistics software version 25. This research uses secondary data by analyzing PT Unilever Indonesia Tbk's quarterly financial reports for the period 2018-2022 obtained through the official website of the Stock Exchange. The method of determining the research sample using a purposive sampling method. The results showed that the current ratio, debt to asset ratio and net profit margin simultaneously affect earnings per share. Meanwhile, the current ratio has a negative and significant effect on earnings per share. Debt to asset ratio and Net profit margin have no effect on earnings per share.